PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK - Sulaeman, Oyib; Wawan, Wawan; Awaliyah, Nurul (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
This study aims to determine the influence of emotional intelligence on the learning achievements of students in MAN 3 Tasikmalaya. The method used in this study is a descriptive method through a quantitative approach, with a population of all MAN 3 Tasikmalaya students and sampling using the area (cluster) sampling technique. Then the data were analyzed using non-parametric statistical types with Spearman Rank correlation. From this study, information was obtained that emotional intelligence has a positive and significant influence on student learning achievement in MAN 3 Tasikmalaya with low classification based on the calculation of the rank Spearman correlation that obtains rs = 0.40 is at the correlation interval0.21-0.40. The influence of emotional intelligence on students' learning achievement at MAN 3 Tasikmalaya has contribution of 16%, the remaining 84% is influenced by other factors namely physiological factors, psychological factors, and environmental influences.